2021
DOI: 10.4081/jphr.2021.2276
|View full text |Cite
|
Sign up to set email alerts
|

Public Knowledge, Attitude and Practice towards Antibiotics Use and Antimicrobial Resistance in Saudi Arabia: A Web-Based Cross-Sectional Survey

Abstract: Background: Antimicrobial resistance is a global issue that causes significant morbidity and mortality. Therefore, this study aims to assess knowledge, attitudes, and practices (KAP) of the general Saudi populations toward antibiotics use.Design and methods: A cross-sectional, anonymous online survey was conducted from January 1 to May 11, 2020, across five major regions of Saudi Arabia. Participants (aged ≥18 years) were invited through social media to complete an online self-structured questionnaire. All dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
23
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 19 publications
(32 reference statements)
8
23
1
Order By: Relevance
“…The number of studies demonstrating the opposite results, where there was an association between a higher monthly income and a better level of knowledge, is limited [ 67 , 69 ]. As in many other studies, this study shows that a high level of education is associated with a better level of knowledge [ 37 , 39 , 44 , 49 , 58 , 69 ]. In Romania, the fact that education influenced the amount of knowledge, but income did not, could be attributed to the fact that education is highly subsidized by the state, up to the highest levels of postgraduate studies, which means that people from all economic and social backgrounds can freely attend higher education.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The number of studies demonstrating the opposite results, where there was an association between a higher monthly income and a better level of knowledge, is limited [ 67 , 69 ]. As in many other studies, this study shows that a high level of education is associated with a better level of knowledge [ 37 , 39 , 44 , 49 , 58 , 69 ]. In Romania, the fact that education influenced the amount of knowledge, but income did not, could be attributed to the fact that education is highly subsidized by the state, up to the highest levels of postgraduate studies, which means that people from all economic and social backgrounds can freely attend higher education.…”
Section: Discussionsupporting
confidence: 87%
“…The excessive use of antibiotics should therefore be avoided by both veterinarians and human doctors, but also by the general population. The reduction in AMR should include measures to educate the public on the efficacy of these substances and their proper use, as demonstrated by numerous studies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Investigating the public knowledge, attitudes and behaviors towards antibiotic use contributes to the organization of effective campaigns to prevent AMR.…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that the knowledge and practice of antibiotics use and AMR is significantly dependent on the education level of the respondents which align with the findings of a study done in Lithuania where people with an education level of a college degree and above had better knowledge, more appropriate behaviours, and better practices [46]. Similarly, the level of income was significantly and synonymously associated with the behaviour and practice of antibiotic use in our study which contrasts with a study performed recently but a similar finding was seen in one of the studies in Saudi Arabia [47,48]. The same study demonstrated a significant association between the nature of work and behaviour and practice on antibiotic use like our study where health professionals were better informed about the correct use of antibiotics.…”
Section: Discussionsupporting
confidence: 86%
“…This issue is becoming more prevalent in low-income African countries [ 19 , 21 ]. On the other hand, the use of antimicrobials can be affected by the interaction of knowledge and expectations of users and prescribers as well as the economic, health systems and environmental factors of the communities [ 16 ]. As a result, a questionnaire survey was used in this study to assess knowledge, practices, and attitudes toward AMU and AMR in Gondar City, Ethiopia.…”
Section: Discussionmentioning
confidence: 99%